LEDS: The Rise of the (Collective) Force — 10 Years of Impact on Innovation and Education in Software Engineering: What we Have Learned by Integrating Teaching, Research, and Extension in Higher Education - Santos Júnior, Paulo Sérgio dos; Calhau, Rodrigo Fernandes; Omena, Moisés Savedra; Oliveira, Felipe Frechiani de; Battestin, Vanessa; Barcellos, Monalessa P. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de Software, 2025)
Over the past decade, the Laboratory for Extension in Development of Solutions (LEDS) has evolved from a small local initiative into an academic ecosystem that integrates teaching, research, and extension in Software Engineering. Founded in 2012 at the Federal Institute of Espírito Santo (IFES), LEDS simulates a real-world software development environment where students engage in multidisciplinary projects that serve public and private sector demands. Through project-based learning and interdisciplinary collaboration, LEDS fosters the development of both technical competencies and essential soft skills, enhancing student engagement and preparing them to face real-world challenges. This paper revisits LEDS over ten years after its inception, highlighting its organizational practices and impacts on student education and institutional innovation, through the creation of a research and extension culture grounded in experiential learning. Finally, we reflect on the lessons learned and challenges and offer practical insights for education professionals and researchers seeking to implement academic software factories as drivers of Software Engineering educational transformation and industry collaboration.